Validez estructural de la escala de autorregulación del aprendizaje para estudiantes universitarios - Chávez Ventura, Gina (2015)
The study’s aim was to obtain evidence of validity of the Learning Self-Regulation Questionnaire (LSRQ) internal structure and to verify metric invariance compared with a previous research study. The participants were 237 university students from the first three academic semesters of a private university in three Peruvian cities (two in the North of Peru, and one in Lima). The analysis was performed by a semi-confirmatory factor analysis, specifying as comparison matrix: a) the configuration derived from a previous study, and b) the free estimation loadings factors. The results indicate that two dimensions represent the instrument structure satisfactorily; but the metric invariance compared to a previous study was not satisfactory. The re-specification of the model, by removing two items with factorial complexity problems and the free estimation of the items, was successful. These results are discussed so as to the interpretation of their scores and the lack of metric invariance.